Cervical Ectopic Pregnancy: A Puzzling Event - Begum, Shahana; Ferdous, Afroza; Sultana, Munawar; Begum, Rowshan Ara (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Cervical ectopic pregnancy is the implantation of the conceptus within the cervix below the level of internal os1. Such pregnancy typically aborts within the first trimester, if it is implanted closer to the uterine cavity called cervico isthmic pregnancy it may continue longer2. Cervical pregnancy accounts for less than 1% of all ectopic pregnancies, with an estimated incidence of 1 in 2500 to 1 in 18000. Though the pregnancy in this area is uncommon but possibly life threatening condition due to risk of severe hemorrhage and may need hysterectomy2,3. Early detection and conservative approach of treatment limit the morbidity and preserve fertility. A 37 year old lady para 4+0 diagnosed as a case of cervical ectopic pregnancy with intractable bleeding and save the patient by emergency hysterectomy to control hemorrhage. The case is reported here for its relative rarity. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21072